Joint Cost Allocation in Determining the Cost of Production in a Small Concrete Manufacturing Enterprise - Hari Karyadi; Galih Wicaksono; Putri Fatmawati (CV. Sakura Digital Nusantara, 2026)
Purpose: This study examines the role of joint cost allocation in determining the cost of production in a small concrete manufacturing enterprise. Accurate cost calculation is essential because it influences pricing decisions, profitability, and business continuity. Design/methodology/approach: This study uses a descriptive qualitative approach. Data were collected through interviews, observation, and documentation involving the business owner and production workers. The analysis focuses on raw materials, direct labor, manufacturing overhead, and the allocation of joint costs across products. Findings/Results: The findings indicate that the company does not fully include several production cost components, particularly mixing labor and overhead costs such as electricity, fuel, and equipment depreciation. As a result, the reported cost of production is lower than the actual cost. Recalculation with proper joint cost allocation provides more accurate production cost information. Originality/Value: This study shows that proper joint cost allocation is important for improving cost accuracy in small manufacturing enterprises. More accurate production cost information can support better pricing, stronger financial management, and more sustainable business decisions